2006
DOI: 10.1021/ed083p1562
|View full text |Cite
|
Sign up to set email alerts
|

Peer-Led Team Learning in Organic Chemistry: Effects on Student Performance, Success, and Persistence in the Course

Abstract: This paper describes the results of instituting peer-led team learning workshop sessions as optional accompaniments for the first two years of chemistry (general chemistry and organic chemistry), courses taught in large-lecture format. About 30% of the students in the courses choose to add this one-credit, two-hour weekly course. Data have been collected for the organic chemistry course over the past five years to compare the outcomes for students who selected workshops with those for students who did not sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 6 publications
(7 reference statements)
4
65
0
2
Order By: Relevance
“…Scientists and engineers work mostly in groups… Similarly, students should gain experiences sharing responsibility for learning with each other .” In addition to learning the skills of working within a group, students often learn and retain more when they work in small groups on projects (e.g. cooperative learning ) versus other instructional formats . BioLEd students experience cooperative learning, the characteristics of which include (i) students working in small groups, (ii) students experiencing shared learning goals (and tasks that may differ from those of other groups), and (iii) grades that are based on both individual work and group work.…”
Section: Facilitating Group Workmentioning
confidence: 99%
“…Scientists and engineers work mostly in groups… Similarly, students should gain experiences sharing responsibility for learning with each other .” In addition to learning the skills of working within a group, students often learn and retain more when they work in small groups on projects (e.g. cooperative learning ) versus other instructional formats . BioLEd students experience cooperative learning, the characteristics of which include (i) students working in small groups, (ii) students experiencing shared learning goals (and tasks that may differ from those of other groups), and (iii) grades that are based on both individual work and group work.…”
Section: Facilitating Group Workmentioning
confidence: 99%
“…Studies have shown improvements in students’ grade performance (Gafney, 2001; Alger and Bahi, 2004; Wamser, 2006) and conceptual reasoning skills (Peteroy-Kelly, 2007). Additional studies indicate positive effects on student retention, with a decreased percentage of PLTL students who fail or withdraw from a course relative to non-PLTL students (Tien et al ., 2002; Wamser, 2006; Stewart et al ., 2007; Hockings et al , 2008).…”
Section: Prior Research On Pltl and Its Benefits For Studentsmentioning
confidence: 99%
“…Additional studies indicate positive effects on student retention, with a decreased percentage of PLTL students who fail or withdraw from a course relative to non-PLTL students (Tien et al ., 2002; Wamser, 2006; Stewart et al ., 2007; Hockings et al , 2008). …”
Section: Prior Research On Pltl and Its Benefits For Studentsmentioning
confidence: 99%
“…Subsequent investigations reviewed in Mitchell, Ippolito and Lewis (7) found that implementing PLTL in a portion of the classes led to increases in common test scores or student retention over traditional lecture-based instruction, while controlling for instructor identity and students' academic background. Most of the research conducted has been performed on PLTL in General Chemistry, but evidence has also shown benefits when PLTL is employed in Organic Chemistry and Biochemistry (5,(7)(8)(9)(10)(11).…”
Section: Peer-led Team Learningmentioning
confidence: 99%